Crafting the Future: A Sustainable Practice of Endek Woven Cloth in Jinengdalem Village, Buleleng District, Bali Province, Indonesia - Arfan, Nadia; Widiawati, Dian; Ardini, Sasanti Puri (Journal of Visual Art and Design, 2024)
While Endek cloth weaving Bali is a long-standing tradition for Balinese people, there is currently an urgency to achieve sustainability. The concern of addressing environmental aspects makes traditional clothing more relevant to the present and future. This paper aims to connect Balinese Endek weaving with natural dyes to preserve the tradition and adapt it to today’s needs. Implementing a participatory approach and collaborating with Poni Songket, the weaver’s community and SME in the Buleleng district of Bali province, this research developed state-of-the-art innovative designs for Balinese Endek weaving by utilizing local potentials such as traditional architecture (paddy and paddy barns) as inspiration for the designs and local natural dyes from the surrounding area for colorization of the fabric. These practices will open advanced opportunities to enhance the community’s economic perspective and expand their knowledge to support sustainable purposes of Indonesia Emas 2045 and the Sustainable Development Goals (SDGs) of the UN.